Empowerment of school teachers for school based injury prevention and safety promotion. (7th October 2012) - Park, N; Yang, H
Abstract : Background: Teachers are key participants for injury prevention and safety promotion in school setting. For participatory programme, it should be identified the teachers' capacities and then developed the empowerment programme based on it. Objectives: The objective is identification of interests, awareness and education and training status on injury prevention and safety promotion of school teachers in Korea. Methods: It was implemented to all schools (K to 12 including special schools) in Korea by web based self-reported survey. The location, level and size of school and teacher's position were applied to survey design. Among 15 103 schools, 7019 schools responded. Questionnaire was developed and revised by literature review, expert discussion and pretest. It is analysed by descriptive statistics using weighting method, χ 2 test and F test. Results: Interests on safety are higher in teachers of kindergarten, special school and manager position (p<0.001). Regarding to nine school safety issues, it is differentiated by variables, especially teacher's position (p<0.001). Training experience is higher in kindergarten, school manager but contents are not helpful for them. Ability on first aid and CPR education is good in lower school level and manager. It is reported to be need mandatory safety education for teachers college and training course. Contribution to the field: It can support for comprehensive identification for teachers programme and be developed and tailored by school and teachers' character for empowerment.